Vận dụng mô hình CIPO vào quản lí đào tạo kĩ năng mềm cho sinh viên các trường Công an nhân dân - Nguyễn Trường Giang, Nguyễn Trường Giang; Dương Thị Kim Oanh, Dương Thị Kim Oanh (Tạp chí Giáo dục, 2026)
In the context of globalization and comprehensive educational reform, the development of soft skills for students of the People’s Public Security has become an urgent requirement, aiming to meet both the learning outcomes of higher education and the specific professional demands of the Public Security forces. This paper analyzes the theoretical and practical foundations of soft skills training while clarifying the relevance of the CIPO model (Context - Input - Process - Output) in training management. The findings indicate that soft skills play a pivotal role in shaping professional competence, enhancing task performance, and building the image of professional public security officers. The application of the CIPO model enables a clear identification of contextual, input, process, and output factors, thereby proposing systematic, scientific, and practice-oriented management solutions. These findings are not only theoretically significant in improving the training model but also contribute to policy and strategic directions for enhancing the quality of human resources in the People’s Public Security in the new era.